Pengembangan Perangkat dan Model Pembelajaran Open Ended Learning Melalui Media Audiovisual dan Media Grafis Pada Materi Media Promosi - Baidlok, Fina Nurul; Irmayanti, Elis; Surindra, Bayu (Efektor, 2020)
This research is motivated by the lack of student achievement levels of a subject due to learning carried out in conventional schools and less creative. This can be seen from the low psychomotor scores of students, which ultimately have an impact on learning outcomes below. In addition, school facilities are not evenly distributed, so that it has an impact on the enthusiasm of students to take part in learning. Therefore, the aim of this research is to find out the process of developing tools and learning models for Open-Ended Learning through audiovisual media and graphic media on promotional media materials for product marketing. This study uses a model research approach with research subjects a team of experts consisting of three people who are experts in why in their respective. The research was carried out in two stages, namely, two times the expert validation test. The results of this development research indicate very good criteria.